Good personality and social well-being: The roles of orientation to happiness - Xu, Xiaodan; Liu, Yang; Jiao, Liying; Wang, Yongming; Yu, Mengke; Lai, Yidie; Zhang, Yingjun; Xu, Yan (Frontiers in Public Health, 2023)
Introduction Positive personality traits have been associated with personal well-being in previous research. However, the pathways through which positive personality may affect social well-being remain unclear. The present study hypothesized that the cognitive strategies for achieving well-being (i.e., orientation to happiness) mediate the association between good personality and social well-being in the Chinese culture. Methods A survey including the Good Personality Questionnaire, Social Well-being Scales, and Orientations to Happiness was administered to 1,503 Chinese secondary school students and adults. Results The results indicated that orientation to meaning mediated the relation between good personality and social well-being, but not orientation to pleasure. Discussion This is in line with the normative well-being model and the cognition instrumental model of well-being, which contributes to developing more targeted interventions to promote social well-being in the Chinese cultural.